Thermal evaluation by infrared measurement of implant site preparation between single and gradual drilling in artificial bone blocks of different densities. Issue 11 (November 2016) - Möhlhenrich, S.C.; Abouridouane, M.; Heussen, N.; Hölzle, F.; Klocke, F.; Modabber, A.
Abstract: The aim of this study was to investigate the influence of bone density and drilling protocol on heat generation during implant bed preparation. Ten single and 10 gradual implant sites with diameters of 2.8, 3.5, and 4.2 mm were prepared in four artificial bone blocks (density types I–IV; D1–D4). Drilling was done at constant speed (1500 rpm) and with external irrigation (50 ml/min); vertical speed was set at 2 mm/s. An infrared camera was used for temperature measurements. Significantly higher temperatures for single drilling were found between 2.8-mm drills in D1 ( P  = 0.0014) and D4 ( P  < 0.0001) and between 3.5-mm drills in D3 ( P  = 0.0087) and D4 ( P  < 0.0001), as well as between 4.2-mm drills in D1 ( P  < 0.0001) and D4 ( P  = 0.0014). Low bone density led to a thermal decrease after single drilling and a thermal increase after gradual drilling. Burs with a large diameter always showed a higher temperature generation. In comparisons between 2.8- and 4.2-mm diameters for both single and gradual drills, significant differences ( P  < 0.001) were noted for bone types II, III, and IV. Single drilling could generate more heat than traditional sequential drilling, and bone density, as well as drill diameter, influenced thermal increases. Particularly in lower-density bone, conventional sequential drilling seems to raise the temperature less.